Multi-Level Authentication: Combining Face, Palm, and Liveness Detection for Improved Security - PV, Raja Suganya; S, Sam Joshua; B, Vigneshwar; M, Jai Kishan (Journal of Innovative Image Processing, 2023)
Face and palm recognition technologies have emerged as powerful tools for authentication, but they can still be vulnerable to fraud and impersonation. Liveness detection is a technique that can detect and prevent fraudulent attempts to bypass authentication by verifying the presence of a live human being during the authentication process. Combining face and palm recognition with liveness detection provides a highly effective and secure approach to authentication, which can prevent fraud and unauthorised access while providing a seamless and user-friendly experience.
Keywords: Face and palm recognition technologies; Liveness detection